2005
DOI: 10.1677/joe.1.05676
|View full text |Cite
|
Sign up to set email alerts
|

Lack of compensatory increase in islet blood flow and islet mass in GK rats following 60% partial pancreatectomy

Abstract: The effects of a 60% partial pancreatectomy were studied in hyperglycemic GK (Goto-Kakizaki) rats. Partial pancreatectomy or a sham operation was performed on 12-weekold female Wistar rats, GK rats or hybrids between male GK rats and female Wistar rats. Measurements of pancreatic blood flow and islet blood flow were performed by a microsphere technique 2 weeks after surgery. Glucose tolerance was decreased in hybrid compared with Wistar rats, and in GK rats compared with both hybrid and Wistar rats before surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…Our findings on GIP effects on glucose homeostasis were thus in line with previous studies and confirm the physiological effects of the used doses (Svensson et al. , ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings on GIP effects on glucose homeostasis were thus in line with previous studies and confirm the physiological effects of the used doses (Svensson et al. , ).…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, during hyperglycemia the highest GIP-dose potentiated glucose-induced insulin secretion. Our findings on GIP effects on glucose homeostasis were thus in line with previous studies and confirm the physiological effects of the used doses (Svensson et al 2000(Svensson et al , 2005.…”
Section: Discussionsupporting
confidence: 92%
“…GK rats might present a deficient angiogenesis due to lack of VEGF response and also possible eNOS uncoupling, because VEGF-induced-eNOS is an efficient pathway of angiogenesis [110], [111] as well as COX-2 [112]. In this context, the lack for GK rats to increase blood flow and islet mass after 60% pancreatectomy as opposed to Wistar rats should be noted [113].…”
Section: Discussionmentioning
confidence: 99%
“…A study on hyperglycemic Goto-Kakizaki (GK) rats showed that following a 60% pancreatectomy, GK rats are unable to compensate for decreased beta-cell mass by increasing islet blood flow in contrast to normal animals [15] . And islet hyperperfusion during the pre-obese and pre-diabetic state was found in a rat model of obesity and type 2 diabetes [16] .…”
Section: Discussionmentioning
confidence: 99%